HELP PHARMACEUTICAL INDUSTRY TO BUILD MEANINGFUL PERSONALIZED HEALTHCARE PROFESSIONAL EXPERIENCE: THE APPLICATION OF THE BRAND LEADERSHIP CIRCLE TOOL TO OPTIMIZE AND INNOVATE ACROSS THE VALUE CHAIN AS PART OF A SUCCESSFUL BUSINESS MODEL - Barreto, Amilcar; Pé-curto, António; Tachibana, Gillian; Lavorgna, Luigi; Gouveia, Pedro; Maida, Elisabetta; Sousa, Conceição; Melo Lopes, Rui Pedro; Joel, Pedro; Bela Cardoso, Patricia; Ribeiro, Eduardo; Guerra, Norberto; et al. (Health and Society, 2024)
Unlike the consumer industry, biopharma, medical technology, and wellness companies have struggled to build meaningful, personalized patient and healthcare professional (HCP) experiences. The increase in drug launches and growing competition across therapy areas has made it challenging for brands and organizations to stand out from the crowd, whether for new molecules vs. legacy brands in an established treatment area and their generic counter-parts or for new molecules in a rare disease where trust is not yet earned. The customers’ needs and preferences are changing at lightning speed. The hierarchy of engagement has transformed, disrupting the dynamic between patients and healthcare professionals. Studies (1, 2) show that drug marketers too often turn various aspects of their product profile into signals – and may inadvertently “reinforce the habitual behavior the marketer is trying to change”. We encourage pharmaceutical companies to use a “data-driven approach to uncover new opportunities for growth” and improvement, and we’re committed to delivering results that make a difference for the patient, HCPs and for the system (value-based healthcare approach). Applying the Brand Leadership Circle, a new strategic tool, will help understand the patients’ journey and other stakeholders’ needs to implement successful approaches in marketing, communications and services using systematic research methods and techniques.